Maternal experienced bereavement and offspring mental health in early adulthood: the role of modifiable parental factors - Rashid, L; Bauer, A; Bowes, L; Creswell, C; Halligan, S (Wiley, 2024)
Background: It is estimated that 78% of children experience the death of a close friend or family member by 16 years of age, yet longitudinal research examining the mental health outcomes of wider experiences of bereavement is scarce. We conducted a longitudinal investigation of the association between maternal experienced bereavement before the age of 11 years and offspring depressive and anxiety disorders at age 18 and examined moderation of this association by modifiable parental factors.